2009
DOI: 10.1590/s1516-80342009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores da evolução do paciente com paralisia cerebral e disfagia orofaríngea após intervenção terapêutica

Abstract: OBJETIVO: Verificar a evolução na função de alimentação e estabilidade clínica de crianças com paralisia cerebral tetraparética espástica após intervenção terapêutica. MÉTODOS: Foram levantados em prontuário médico, antes e após a terapia, os dados de classificação da funcionalidade da alimentação (escala FOIS) e grau de disfagia, consistências alimentares e sinais sugestivos de penetração e/ou aspiração laringotraqueal de 36 crianças com paralisia cerebral espástica. RESULTADOS: A maioria dos sujeitos aliment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
0
5
0
7
Order By: Relevance
“…It was found that the higher is the motor level of the group of children, the longer is the swallowing time for the liquid consistency and a significant difference was found between the groups for both consistencies, with progressive increase of the swallowing time the greater the impairment of the swallowing function. Oral transit time in children with cerebral palsy was higher and represented the severity of the dysphagia presented, demonstrating that the greater is the overall motor impairment presented, the longer is the oral transit time 1,3,9,11,[13][14][15][16][17][18][19][20] .…”
Section: Figure 2 Articles Analyzed In the Systematic Reviewmentioning
confidence: 99%
“…It was found that the higher is the motor level of the group of children, the longer is the swallowing time for the liquid consistency and a significant difference was found between the groups for both consistencies, with progressive increase of the swallowing time the greater the impairment of the swallowing function. Oral transit time in children with cerebral palsy was higher and represented the severity of the dysphagia presented, demonstrating that the greater is the overall motor impairment presented, the longer is the oral transit time 1,3,9,11,[13][14][15][16][17][18][19][20] .…”
Section: Figure 2 Articles Analyzed In the Systematic Reviewmentioning
confidence: 99%
“…Yogurt was called thin pasty by most of the speech-language pathologists and thick pasty by most nutritionists. In the investigated national literature, three references (11,12,23) applied the term thin pasty, but only one of them (11) exemplified the food used for this texture, Bliss ® yogurt. The same happened with the term thick pasty, exemplified with Danete ® food, in only one of the references (11) .…”
Section: Discussionmentioning
confidence: 99%
“…A função de mastigação não é eficiente nestas crianças, fazendo com que estes alimentos sejam deglutidos inteiros, ou mesmo aumentando o tempo de manipulação oral do bolo, deixando a refeição com maior gasto energético 11 . Dessa maneira, a alimentação na consistência sólida não foi considerada e descrita nessa pesquisa, pois dos vinte pacientes avaliados apenas cinco conseguiam ingerir alimentos sólidos sem apresentar risco de aspiração traqueal ou estase em recessos faríngeos.…”
Section: Métodounclassified
“…A persistência do movimento de sucção com a língua nas crianças com PC, além de dificultar a aquisição de movimentos mais adequados de língua, quando acompanhados de hiper ou hipossensibilidade oral, também conduz a dificuldade de mastigar e deglutir alimentos 11 . Estudar a eficácia da fonoterapia para disfagia em crianças com distúrbios neurológicos é tarefa complexa devido à quantidade de sintomas associados que apresentam 5,[19][20] .…”
Section: Tabela 4 -Avaliação Funcional Da Deglutição Após Intervençãounclassified
See 1 more Smart Citation